Existence of solution to a periodic boundary value problem for a nonlinear impulsive fractional differential equation - Mohammed Belmekki; Juan Nieto; Rosana Rodríguez-López (Electronic Journal of Qualitative Theory of Differential Equations, 2014)
We study the existence of solution to a periodic boundary value problem for nonlinear impulsive fractional differential equations by using Schaeffer’s ﬁxed point theorem.